2022
DOI: 10.1007/s13311-022-01261-4
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Metastases: New Opportunities in the Modern Era

Abstract: Leptomeningeal metastases arise from cancer cell entry into the subarachnoid space, inflicting significant neurologic morbidity and mortality across a wide range of malignancies. The modern era of cancer therapeutics has seen an explosion of molecular-targeting agents and immune-mediated strategies for patients with breast, lung, and melanoma malignancies, with meaningful extracranial disease control and improvement in patient survival. However, the clinical efficacy of these agents in those with leptomeningea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 184 publications
0
8
0
Order By: Relevance
“…One unique and novel treatment modality that is currently undergoing research is the depletion of one specific nutrient in the CSF, iron. Given that LC is anatomically devoid of a blood-tumor capillary network, it is found that free iron in the CSF is one of the main nutrients that LC survives off [ 18 ]. An iron-binding transporter that is possessed by cancer cells is lipocalin-2, along with its receptor, SLC22A17 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One unique and novel treatment modality that is currently undergoing research is the depletion of one specific nutrient in the CSF, iron. Given that LC is anatomically devoid of a blood-tumor capillary network, it is found that free iron in the CSF is one of the main nutrients that LC survives off [ 18 ]. An iron-binding transporter that is possessed by cancer cells is lipocalin-2, along with its receptor, SLC22A17 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that LC is anatomically devoid of a blood-tumor capillary network, it is found that free iron in the CSF is one of the main nutrients that LC survives off [ 18 ]. An iron-binding transporter that is possessed by cancer cells is lipocalin-2, along with its receptor, SLC22A17 [ 18 ]. Current pre-clinical studies in mice show that by restricting the cancer cells from iron by intrathecal administration of an iron chelator, deferoxamine, there is an observed reduction in tumor burden correlated with prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our patient, the last test showed a serum value of 492.There are currently several treatment modalities for LM. Intrathecal chemotherapy, whole‐brain radiation therapy (WBRT), radiation therapy for spinal cord disease (RT), and CNS‐sensitive chemotherapy regimens can be selected 23 . LM represents an advanced disease with a short survival time and an aggressive clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Leptomeningeal disease (LMD) occurs when cancer cells metastasize from an original tumor site into the cerebrospinal fluid (CSF) that occupies the subarachnoid space between the pia and arachnoid mater layers of the meninges that surround the central nervous system [ 1 , 2 , 3 , 4 ]. LMD comprises up to 8% of solid and 15% of hematological malignancies, with over 100,000 new cases annually in the United States, and has a very poor prognosis with a median survival of 3–16 weeks despite treatment [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%